Determinantes económicos de la producción agrícola y su incidencia en las exportaciones agroindustriales de la región La Libertad, período: 2010-2017 - Barriga Yglesias, Lizseth Gianella (2019)
The present study investigates the economic determinants of agricultural production and its impact on agroindustrial exports of the La Libertad region, during the period 2010 - 2017. An analysis was carried out on the main consuming countries of agricultural products of the La Libertad Region during the period 2010 and 2017, among them: The United States was the country that consumes the most agricultural products, followed by Spain, Ecuador, Holland and France, being these the potential consumers of agricultural products produced in the La Libertad Region. Then, the main economic variables that affect agricultural exports were identified, of which are: the real exchange rate and private consumption, the terms of trade and public spending in the agricultural sector. In addition, a double-logarithmic econometric model was formulated where the incidence of each economic determinant of agricultural production was estimated (The Per Capita Gross Domestic Product of the United States, the real exchange rate, terms of trade and public spending in the agricultural sector). Finally, it was determined that the real exchange rate and the Per Capita Gross Domestic Product of the United States affect agricultural production in the agroindustrial exports of the La Libertad region, and the terms of trade and public expenditure in the agro-industrial sector do not they have significant effects, for which reason, the four variables in question explain 87.60% of the agroindustrial exports of the La Libertad Region, according to the model estimated under ordinary minimum squares.